Horndon-on-the-Hill, Essex: a morphological analysis of the Late Saxon and medieval settlement - Secker, Daniel (Medieval Settlement Research, 2023)
Horndon-on-the-Hill (centring on TQ67058352), hereafter simply ‘Horndon’, is a former small medieval market town with suspected origins as a late Saxon fortified settlement (Rippon 1996, 121–22; Essex County Council 2006, 7–9, 21–22). It is situated in southern Essex, some 35 km east of London and just to the north of the Thames estuary (Fig. 1a). Horndon occupies one of a number of low hills which are isolated features in an otherwise flat landscape (Fig. 1b). The latter is part of the topographical zone or pays of the Lower Thames Terraces which form a distinct contrast with the hilly pays of the South Essex London Clay District to the north (Rippon et al. 2015, 125). Horndon is situated on a prominent crescentic or ‘horn-shaped’ hill from which it derives its name (Fig. 2). The hill is on the London Clay Formation (British Geological Survey 1996). Neighbouring parishes are Mucking to the south, Orsett to the west, Laindon Hills to the north and Stanford-le-Hope to the east, the last originating as the Domesday estate of Hassenbrook (Williams and Martin 2002, 986; Kemble 2015, 5). The latter takes its name from the stream dividing Horndon from Stanford.